HUBUNGAN ANTARA DEPENDENT-CARE AGENCY DENGAN PERILAKU ORANG TUA DALAM PEMBERIAN MAKAN PADA ANAK USIA 1 - 3 TAHUN DI WILAYAH PUSKEMAS DEPOK III SLEMAN YOGYAKARTA - , ARINDA NIVIANITA SARI; , Lely Lusmilasari, S.Kp., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Parentsâ behavior ini feeding children is an important factor in the fulfillment of adequate nutrition intake, optimalization of health and well-being of children of 1 â 3 years. Parents are supposed to have ability to be gatekeeper of childâs eating pattern and role model for childâs eating behavior. Such an ability is closely related to knowledge, skills and motivation of parents in the fulfillment of childrenâs needs called dependent-care agency (DCA). Objective: The objective of the study was to identify correlation between DCA and parentsâ behavior in feeding children of 1 â 3 years. Method: The Study was observational with correlation analytic method and cross sectional undertaken in Oktober â Desember 2012. Samples of the study were parents with children of 1 â 3 yaers old at the area of Depok III Health Center Sleman Yogyakarta as manyas 85 respondents taken through total sampling techniques. The selection of subdistrict and integrated service post as location of the study was based on lottery technique. Research instrument was modifed by Denyes/Fildey Dependent-Care Agency instrument and questionnaire of parentsâ behaviour in feeding the children used modified by Moore Index of Nutrition- Parent (MIN-P). Data analysis used univariate, bivariate, Spearman-Rho and SPSS 17. Result: The result of correlation showed significance between score dependentcare agency and parentsâ behavior in feeding children of 1 â 3 years with score p = 0,003 and r = 0,315 that correlation was weakly positive. Conclusion: There was significant correlation between dependent-care agency and parentsâ behavior in feeding children of 1 â 3 years. Thus, parents had to improve dependent-care agency to show optimum behavior in feeding children. Furthur this study was supposed to consider other variables not included in this study.